Cara de um, focinho do outro. As transformações do pet keeping e suas implicações nas práticas de consumo envolvidas nas relações entre idosos (as) e seus cães - Silva, Helton Rodolfo Mendes Leal da (2020)
Mans and animals always had a close relationship, but over time, this relationship changed, according with a phenomenon known as pet keeping, which gave the animal the status of pet and member of the family arrangement, occupying a significant space in the relationships and directly influencing consumer practices. Add to this phenomenon, in contemporary times, the ageing of the population, with exponential growth and gives new meaning to “ageing”, allowing the elderly to remain active in consumer relations and protagonist in social relations. When we combine these two great phenomena, we find an object of extreme interest, whether for consumer studies, for industry and retail, given its market significance, both in Brazil and in the world. Thus, understanding these new relationships, and the group of practices that can be identified from them, we will call transformation of pet keeping, and our goal is to characterize the consumption behaviors within the scope of the pet keeping practice of elderly dog tutors in the state of São Paulo. We conducted a qualitative research, with data collection through diaries of the routine of elderly tutors, which were later triangulated with in-depth interviews and interpreted under the lens of the theory of practice. As a result, we found as the main evidence of this transformation, the transcendence of the dog in relation to the role of companionship, starting to occupy a more prominent place in the life of the tutor, as a member of the family arrangement. Resulting, the products and services consumed have been transformed, giving rise to new practices, products and meanings of consumption, impacting on the routine of both, especially in the food field.